The blue diamond [large type] - Goldberg, Leonard, 1936- (Goldberg, Leonard, 1936- Daughter of Sherlock Holmes mystery, 2024)
"During a critical stage in World War I, the Governor-General of South Africa journeys to London for a meeting of The Imperial War Conference. Days prior to the conference, the Governor-General is scheduled to have an audience at Buckingham Palace at which time a most precious blue diamond will be presented to King George as a symbolic gesture of the colonies' resolute and never-ending allegiance to England. The flawless blue diamond, with its magnificent luster, weighs nearly 3000 carats which renders it one of the world's largest and most valuable gems. On the Governor-General's arrival, he is ensconced at the fashionable Windsor Hotel under the tightest security, with his entire entourage and formidable security team occupying the entire penthouse floor. All entrances and exits are locked down and closely guarded, and no one is allowed entrance after 6 PM. Despite the extreme precautions, the famous diamond is stolen from the Governor-General's suite in the middle of the night, with no clues left behind. With Scotland Yard baffled, Joanna and the Watsons are called in to investigate the theft and it becomes clear that the crime is not simply the work of a master thief, but one that could greatly aid the Germans and turn the tide of war in their favor. Time is of the essence and the blue diamond must be recovered before it causes irreparable damage to the allied war plans."--